La difusión de noticias falsas en medios de comunicación digital y la responsabilidad penal del comunicador - Fabián David, Vayas Vayas (2021)
ABSTRACT The responsibility that the communicator may have for the dissemination of false news through the media is an issue of high social relevance, since on several occasions the affectation that occurs in society by spreading false news has been evidenced, as It is common that the digital news that is disseminated does not have a verified and reliable source, which also gives rise to an attack on the honor and good name of hundreds of people. It is for this reason that there is a need to classify this conduct, because despite the fact that in the Comprehensive Organic Criminal Code there are offenses against the right to honor and good name, it is necessary that there be a criminal type that sanctions the dissemination of false information by digital means with a penalty higher than that of slander or libel offenses; Since, at present the news published in digital media is disseminated both nationally and internationally. Therefore, in order for there to be a joint development of Law with technology and society, the existing legal vacuum with respect to the dissemination of false news in digital media must be covered, since the inherent legal good of every human being is not being protected, as is the right to honor and good name, in order to fulfill the feat of providing society with information that is of real help in order to have a better development. KEYWORDS: Criminal liability, digital media, violation of rights.